1999
DOI: 10.1091/mbc.10.7.2361
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mayven, a Novel Actin-binding Protein Predominantly Expressed in Brain

Abstract: The cytoskeleton plays an important role in neuronal morphogenesis. We have identified and characterized a novel actin-binding protein, termed Mayven, predominantly expressed in brain. Mayven contains a BTB (broad complex, tramtrack, bric-a-brac)/POZ (poxvirus, zinc finger) domain-like structure in the predicted N terminus and "kelch repeats" in the predicted C-terminal domain. Mayven shares 63% identity (77% similarity) with the Drosophila ring canal ("kelch") protein. Somatic cell-hybrid analysis indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 48 publications
4
96
2
Order By: Relevance
“…It should also be noted that when Krp1-myc was expressed in 208F cells, and when we examined the low level of endogenous Krp1 that is present in FBR-TAM67 cells, no co-localization with F-actin containing stress Âźbres was detected. This result contradicts work presented by Hernandez et al, (1997) and Soltysik-Espanola et al (1999), who reported that two other kelch family members, ENC1 and Mayven, interact with stress Âźbres containing F-actin. Together these data suggest that Krp1 only co-localizes with F-actin when it is in the looped membrane ru e-like structure at the tips of pseudopodia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It should also be noted that when Krp1-myc was expressed in 208F cells, and when we examined the low level of endogenous Krp1 that is present in FBR-TAM67 cells, no co-localization with F-actin containing stress Âźbres was detected. This result contradicts work presented by Hernandez et al, (1997) and Soltysik-Espanola et al (1999), who reported that two other kelch family members, ENC1 and Mayven, interact with stress Âźbres containing F-actin. Together these data suggest that Krp1 only co-localizes with F-actin when it is in the looped membrane ru e-like structure at the tips of pseudopodia.…”
Section: Discussioncontrasting
confidence: 99%
“…Another protein, alpha-scruin of Limulus, which has kelch repeats present at both its amino and carboxyl termini but lacks a BTB/POZ domain, cross-links actin Âźlaments within the acrosomal processes of sperm (Way et al, 1995a). Further kelch proteins are also thought to interact with actin: murine and human ENC1 (Hernandez et al, 1997(Hernandez et al, , 1998; spe-26 of C. elegans (Varkey et al, 1995); and human Mayven (Soltysik-Espanola et al, 1999). Many other family members are thought not to interact with actin; beta-scruin of Limulus, for instance, is found in sperm acrosomal vesicles, which do not contain actin (Way et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTB/kelch proteins are highly conserved across species, yet their functional roles appear quite diverse, ranging from organization of cytoskeletal elements to control of protein trafficking/ ubiquitination and regulation of gene expression. Two brain-enriched BTB/kelch proteins closely related to KRIP6, Mayven and actinfilin, associate with the actin cytoskeleton (Chen et al, 2002;Soltysik-Espanola et al, 1999). However, unlike Mayven and actinfilin, KRIP6 does not colocalize with F-actin in COS-7 cells or in neurons, and thus probably does not bind actin.…”
Section: Discussionmentioning
confidence: 99%
“…The BTB/POZ domain is a zinc finger and protein-protein interaction domain (Li et al, 1997) known to dimerize (e.g. (Cullen et al, 2004;Soltysik-Espanola et al, 1999). The kelch repeats, each four antiparallel ÎČ strands of 44-56 aa, combine to generate a ÎČ-propeller structure (Adams et al, 2000).…”
Section: Krip6 Is a Btb/kelch Protein Interacting With Glur6mentioning
confidence: 99%